2021
DOI: 10.1136/bmjpo-2021-001147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic psychological stress reactions in children and parents following paediatric surgery: a systematic review and meta-analysis

Abstract: BackgroundChildren undergoing surgery and their parents are at risk of developing post-traumatic stress reactions. We systematically reviewed the literature to understand the prevalence of this issue, as well as potential risk factors.MethodsWe conducted a systematic review and meta-analysis, using PubMed, PsycInfo, Web of Science and Google Scholar, with searches conducted in February 2021. Papers were included if they measured post-traumatic stress in children and/or parents following paediatric surgery and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…45,46 Like our findings, Turgoose et al did not find significant demographic or clinical factors that predict post-traumatic stress disorder in parents of children with CHD (any type) undergoing bypass. 45 Parents need support and education to help them adapt to the stress and challenge of raising a child with critical CHD. 47,48 Healthcare professionals are in a unique position to have a positive influence on how parents adapt to stressors by recognising symptoms in parents and referring parents to appropriate resources.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…45,46 Like our findings, Turgoose et al did not find significant demographic or clinical factors that predict post-traumatic stress disorder in parents of children with CHD (any type) undergoing bypass. 45 Parents need support and education to help them adapt to the stress and challenge of raising a child with critical CHD. 47,48 Healthcare professionals are in a unique position to have a positive influence on how parents adapt to stressors by recognising symptoms in parents and referring parents to appropriate resources.…”
Section: Discussionsupporting
confidence: 75%
“…2,4,43 Our study showed that demographic and clinical (medical or surgical) factors such as pre-natal diagnosis, complications, and length of hospital stay did not identify which parents were at greater risk to develop post-traumatic stress disorder symptoms, a finding supported by other studies. 44,45 Measures of anxiety have been associated with elevated post-traumatic stress disorder symptoms in parents of children with CHD. 45,46 Like our findings, Turgoose et al did not find significant demographic or clinical factors that predict post-traumatic stress disorder in parents of children with CHD (any type) undergoing bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A systematic review found an increased risk of traumatic psychological stress reactions following paediatric surgery, for both the children and the parents. 7 The European network for surveillance of congenital anomalies (EUROCAT) comprises population-based congenital anomaly registries in 23 countries covering more than 1.7 million (29%) of European births per year. 8 To investigate the survival and morbidity of children with major congenital anomalies, members of the EUROCAT registries initiated the EUROlinkCAT project.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal surgery also has an impact on family bonding and the initiation of breastfeeding 5,6 . A systematic review found an increased risk of traumatic psychological stress reactions following paediatric surgery, for both the children and the parents 7 …”
Section: Introductionmentioning
confidence: 99%